Ditadura militar e literatura “parajornalística”: desconstruindo relações - Sabrina Schneider (Universidade de Brasília, 2014)
This article proposes a new approach to the Brazilian nonfiction novel from the seventies. It is understood that, in their appreciation of these works, academic literary critics considered only the impact of national political situation – the military dictatorship –, taking up these narratives as mere substitutes for censored newspapers. It was therefore disregarded the difference between news, product of daily informative journalism, and literary journalism, a journalistic genre that has no place in the mainstream press. While the former doesn’t include narration, the latter develops characters and builds a plot, establishing a fictional universe as accepted by authors such as Paul Ricoeur, Mikhail Bakhtin, and Käte Hamburger.